Formação e prática pedagógica de professores da EJA junto a estudantes com deficiência intelectual - Tassinari, Ana Maria (2019)
This study aimed at analyzing the formation and acting of Adult Education teachers regarding intellectually disabled students. As specific objectives, this study aimed at: (a) characterizing the formation of Adult Education teachers and their knowledge about special education; (b) identifying the demands of Adult Education teachers concerning their acting with intellectually disabled students; (c) developing a formation program for Adult Education teachers, aiming at a reflexive process of the teaching practice in an inclusive context. In order to do so, we relied on the systematization of the collaborative action research with qualitative approach. This study was held in a municipality of the northern region of the State of São Paulo. Participated in this research seven Adult Education teachers who act in Elementary School and work with intellectually disabled students. Based on the intended objectives, the data collection was organized in three phases: characterization of the pedagogical practice, identification of the teachers’ demands and Reflexive Formation. The instuments used for collecting data developed by the researcher were: (a) observation script in class, (b) semistructured interview script for Adult Education teachers acting with intellectually disabled students, (c) field diary, (d) virtual classroom, and (e) reflexive formation. With the collected data, we used the category content analysis technique, which were analyzed and organized. The results show aspects related to: Adult Education teachers formation and knowledge in special education; teachers’ conception and experience about inclusion in Adult Education; organization and teaching in Adult Education with intellectually disabled students; and contributions of reflexive formation for teaching. Results showed that teachers do not feel prepared to inclusion because of the lack of a theoretical, technical and methodological preparation. Also, they support of specialized professionals to monitor and guide students, persisting, still, in a traditional practice, with expository lessons, using practices which are not proper to inclusion. About reflexive formation, teachers indicate contributions of the formative process to teaching reflexion, specially regarding practices and perceptions with intellectually disabled students.